Current–voltage characteristics of single-molecule diarylethene junctions measured with adjustable gold electrodes in solution - Briechle, Bernd M.; Kim, Youngsang; Ehrenreich, Philipp; Erbe, Artur; Sysoiev, Dmytro; Huhn, Thomas; Groth, Ulrich; Scheer, Elke (Beilstein Journal of Nanotechnology, 2012)
We report on an experimental analysis of the charge transport through sulfur-free photochromic molecular junctions. The conductance of individual molecules contacted with gold electrodes and the current–voltage characteristics of these junctions are measured in a mechanically controlled break-junction system at room temperature and in liquid environment. We compare the transport properties of a series of molecules, labeled TSC, MN, and 4Py, with the same switching core but varying side-arms and end-groups designed for providing the mechanical and electrical contact to the gold electrodes. We perform a detailed analysis of the transport properties of TSC in its open and closed states. We find rather broad distributions of conductance values in both states. The analysis, based on the assumption that the current is carried by a single dominating molecular orbital, reveals distinct differences between both states. We discuss the appearance of diode-like behavior for the particular species 4Py that features end-groups, which preferentially couple to the metal electrode by physisorption. We show that the energetic position of the molecular orbital varies as a function of the transmission. Finally, we show for the species MN that the use of two cyano end-groups on each side considerably enhances the coupling strength compared to the typical behavior of a single cyano group.
Keywords: diarylethene; mechanically controllable break-junction; molecular electronics; photoswitching; single-molecule junctions

(untitled) - Nitzan, A.; Ratner, M. A. (Science, 2003)

Molecular electronics: an introduction to theory and experiment - Cuevas, J. C.; Scheer, E. (World Scientific, 2010)

(untitled) - del Valle, M.; Gutiérrez, R.; Tejedor, C.; Cuniberti, G. (Nat. Nanotechnol., 2007)

(untitled) - Song, H.; Kim, Y.; Jang, Y. H.; Jeong, H.; Reed, M. A.; Lee, T. (Nature, 2009)

(untitled) - Dulić, D.; van der Molen, S. J.; Kudernac, T.; Jonkman, H. T.; de Jong, J. J. D.; Bowden, T. N.; van Esch, J.; Feringa, B. L.; van Wees, B. J. (Phys. Rev. Lett., 2003)

(untitled) - Park, H.; Park, J.; Lim, A. K. L.; Anderson, E. H.; Alivisatos, A. P.; McEuen, P. L. (Nature, 2000)

(untitled) - Lörtscher, E.; Ciszek, J. W.; Tour, J.; Riel, H. (Small, 2006)

(untitled) - Xu, B.; Xiao, X.; Yang, X.; Zang, L.; Tao, N. (J. Am. Chem. Soc., 2005)

(untitled) - Chen, F.; He, J.; Nuckolls, C.; Roberts, T.; Klare, J. E.; Lindsay, S. (Nano Lett., 2005)

(untitled) - Pobelov, I. V.; Li, Z.; Wandlowski, T. (J. Am. Chem. Soc., 2008)

(untitled) - Kim, Y.; Song, H.; Strigl, F.; Pernau, H. F.; Lee, T.; Scheer, E. (Phys. Rev. Lett., 2011)

(untitled) - Kim, Y.; Pietsch, T.; Erbe, A.; Belzig, W.; Scheer, E. (Nano Lett., 2011)

(untitled) - Li, C.; Pobelov, I.; Wandlowski, T.; Bagrets, A.; Arnold, A.; Evers, F. (J. Am. Chem. Soc., 2008)

(untitled) - Zhu, L.; Yao, K. L.; Liu, Z. L. (Appl. Phys. Lett., 2010)

(untitled) - Matsuda, K.; Irie, M. (J. Am. Chem. Soc., 2000)

(untitled) - Jo, M.; Grose, J. E.; Baheti, K.; Deshmukh, M. M.; Sokol, J. J.; Rumberger, E. M.; Hendrickson, D. N.; Long, J. R.; Park, H.; Ralph, D. C. (Nano Lett., 2006)

(untitled) - Bogani, L.; Wernsdorfer, W. (Nat. Mater., 2008)

(untitled) - van der Molen, S. J.; Liao, J. N.; Kudernac, T.; Agustsson, J. S.; Bernard, L.; Calame, M.; van Wees, B. J.; Feringa, B. L.; Schönenberger, C. (Nano Lett., 2009)

(untitled) - de Jong, J. J. D.; Lucas, L. N.; Kellogg, R. M.; van Esch, J. H.; Feringa, B. L. (Science, 2004)

(untitled) - Irie, M.; Kobatake, S.; Horichi, M. (Science, 2001)

(untitled) - Kronemeijer, A. J.; Akkerman, H. B.; Kudernac, T.; van Wees, B. J.; Feringa, B. L.; Blom, P. W. M.; de Boer, B. (Adv. Mater., 2008)

(untitled) - Uchida, K.; Yamanoi, Y.; Yonezawa, T.; Nishihara, H. (J. Am. Chem. Soc., 2011)

(untitled) - Whalley, A. C.; Steigerwald, M. L.; Guo, X.; Nuckolls, C. (J. Am. Chem. Soc., 2007)

(untitled) - Katsonis, N.; Kudernac, T.; Walko, M.; van der Molen, S. J.; van Wees, B. J.; Feringa, B. L. (Adv. Mater., 2006)

(untitled) - He, J.; Chen, F.; Liddell, P. A.; Andréasson, J.; Straight, S. D.; Gust, D.; Moore, T. A.; Moore, A. L.; Li, J.; Sankey, O. F.; Lindsay, S. M. (Nanotechnology, 2005)

(untitled) - Tam, E. S.; Parks, J. J.; Shum, W. W.; Zhong, Y.; Santiago-Berríos, M. B.; Zheng, X.; Yang, W.; Chan, G. K.-L.; Abruña, H. D.; Ralph, D. C. (ACS Nano, 2011)

(untitled) - Park, Y. S.; Widawsky, J. R.; Kamenetska, M.; Steigerwald, M. L.; Hybertsen, M. S.; Nuckolls, C.; Venkataraman, L. (J. Am. Chem. Soc., 2009)

(untitled) - Zhuang, M.; Ernzerhof, M. (J. Chem. Phys., 2009)

(untitled) - Boscoboinik, J. A.; Kohlmeyer, R. R.; Chen, J.; Tysoe, W. T. (Langmuir, 2011)

(untitled) - Sysoiev, D.; Fedoseev, A.; Kim, Y.; Exner, T. E.; Boneberg, J.; Huhn, T.; Leiderer, P.; Scheer, E.; Groth, U.; Steiner, U. E. (Chem.–Eur. J., 2011)

(untitled) - Sysoiev, D.; Yushchenko, T.; Scheer, E.; Groth, U.; Steiner, U. E.; Exner, T. E.; Huhn, T. (Chem. Commun., 2012)

(untitled) - Kim, Y.; Hellmuth, T. J.; Sysoiev, D.; Pauly, F.; Pietsch, T.; Wolf, J.; Erbe, A.; Huhn, T.; Groth, U.; Steiner, U. E.; Scheer, E. (Nano Lett., 2012)

(untitled) - Zotti, L. A.; Kirchner, T.; Cuevas, J.-C.; Pauly, F.; Huhn, T.; Scheer, E.; Erbe, A. (Small, 2010)

(untitled) - Huisman, E. H.; Guédon, C. M.; van Wees, B. J.; van der Molen, S. J. (Nano Lett., 2009)

(untitled) - Grüter, L.; Cheng, F. Y.; Heikkilä, T. T.; González, M. T.; Diederich, F. O.; Schönenberger, C.; Calame, M. (Nanotechnology, 2005)

(untitled) - Grüter, L.; González, M. T.; Huber, R.; Calame, M.; Schönenberger, C. (Small, 2005)

(untitled) - Tsuji, Y.; Staykov, A.; Yoshizawa, K. (J. Phys. Chem. C, 2009)

(untitled) - Venkataraman, L.; Klare, J. E.; Tam, I. W.; Nuckolls, C.; Hybertsen, M. S.; Steigerwald, M. L. (Nano Lett., 2006)

(untitled) - Martin, C. A.; Ding, D.; Sørensen, J. K.; Bjørnholm, T.; van Ruitenbeek, J. M.; van der Zant, H. S. J. (J. Am. Chem. Soc., 2008)

(untitled) - Büttiker, M.; Imry, Y.; Landauer, R.; Pinhas, S. (Phys. Rev. B, 1985)

(untitled) - Hong, W.; Valkenier, H.; Mészáros, G.; Manrique, D. Z.; Mishchenko, A.; Putz, A.; García, P. M.; Lambert, C. J.; Hummelen, J. C.; Wandlowski, T. (Beilstein J. Nanotechnol., 2011)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Lavrich, D. J.; Wetterer, S. M.; Bernasek, S. L.; Scoles, G. (J. Phys. Chem. B, 1998)

(untitled) - Kühnle, A. (Curr. Opin. Colloid Interface Sci., 2009)

(untitled) - Kim, Y.; Hellmuth, T. J.; Bürkle, M.; Pauly, F.; Scheer, E. (ACS Nano, 2011)

(untitled) - Quek, S. Y.; Kamenetska, M.; Steigerwald, M. L.; Choi, H. J.; Louie, S. G.; Hybertsen, M. S.; Neaton, J. B.; Venkataraman, L. (Nat. Nanotechnol., 2009)

(untitled) - Zhou, X.-S.; Chen, Z.-B.; Liu, S.-H.; Jin, S.; Liu, L.; Zhang, H.-M.; Xie, Z.-X.; Jiang, Y.-B.; Mao, B.-W. (J. Phys. Chem. C, 2008)

(untitled) - Stolberg, L.; Morin, S.; Lipkowski, J.; Irish, D. E. (J. Electroanal. Chem., 1991)

(untitled) - Solomun, T.; Christmann, K.; Baumgaertel, H. (J. Phys. Chem., 1989)

(untitled) - Mishchenko, A.; Zotti, L. A.; Vonlanthen, D.; Bürkle, M.; Pauly, F.; Cuevas, J. C.; Mayor, M.; Wandlowski, T. (J. Am. Chem. Soc., 2011)

(untitled) - Böhler, T.; Edtbauer, A.; Scheer, E. (New J. Phys., 2009)

(untitled) - van Ruitenbeek, J. M.; Alvarez, A.; Piñeyro, I.; Grahmann, C.; Joyez, P.; Devoret, M. H.; Esteve, D.; Urbina, C. (Rev. Sci. Instrum., 1996)